Spatial and Temporal Variability of Coastal Carbonate Chemistry in the Southern California Region - Davidson, Charles Woodruff (eScholarship, University of California, 2015)
The objective of this study was to characterize temporal and spatial variability in near shore inorganic carbon chemistry in Southern California. To date, relatively little research has been conducted concerning seawater carbon chemistry in the near-shore environment (<2 miles from shore), and this study attempts to serve as a starting point to better understand the contemporary conditions and variability in this environment. Seawater samples were collected monthly for a one-year duration at 15 near-shore locations, encompassing sandy beaches, rocky beaches, and harbors or bays in the San Diego area. This approach was complemented by sampling from a boat along an offshore running transect in La Jolla Cove at 4 locations from the surface to 40m depth. Measurements of Dissolved Inorganic Carbon (DIC), Total Alkalinity (TA), Temperature, and Salinity were conducted. These measured parameters were used to calculate in situ pHSWS, aragonite saturation state ([Omega]-aragonite), pCO₂, and air-sea CO₂ flux at all locations where applicable. Sample locations were categorized, based on their localized environment, into three categories: beach/sand, beach/rock, and harbor/bay (Figure 1). In general, we observed large spatial and temporal variability in DIC, TA, pHSWS, [Omega]-aragonite, pCO₂, and CO₂ flux. The highest variability, as well as the largest values in DIC and TA, occurred in stations categorized as bay/harbor. Stations categorized as beach/ sand and beach/rock were less variable, although, compared to open ocean environments they still experienced large variability with averages of DIC ranging from ±40 µmol kg⁻¹ to ±100 µmol kg⁻¹ over the 12-month study period. Notably, we observed an overall region-wide decrease in TA that contributed to lower seawater pHSWS and [Omega]- aragonite during spring and summer. Calculated pCO₂ and CO₂ flux showed that the region acted as a source of CO₂ to the atmosphere, result that is consistent with previous studies, which have shown that inner continental shelves in general serve as sources of CO₂ to the atmosphere. Low surface seawater pH and [Omega]-aragonite were occasionally observed at some of the stations (sometimes as low as 7.51 and 1.0, respectively), showing a worrying level of acidity not expected in the open ocean until the end of the next century. Similarly, the coastal offshore transect revealed shoaling of low seawater pH and [Omega]- aragonite in the spring and summer as a result of intensified upwelling during this time period. These observations show how coastal processes are likely to intensify the effects of ocean acidification in the coastal ocean with potential consequences to marine organisms sensitive to changes in seawater pH and [Omega]- aragonite. In conclusion, this study provides key data showing that the near-shore environment is highly variable and on occasion experience seawater CO₂ conditions not expected in the open ocean until well into the future. It acts as starting point for further studies aiming to understand the complexity of the near-shore environments that is of major economic, ecologic, scientific, and social importance